THE TRANSFORMATION OF MULTIMEDIA-BASED CHARACTER EDUCATION LEARNING IN THE ERA OF SOCIETY 5.0: A Case Study Of Madrasah Aliyah Pondok Pesantren Ar Rahman Palembang - Arnensi, Arnensi; Abdurrahmansyah, Abdurrahmansyah; Elhefni, Elhefni (Conciencia, 2023)
The purpose of this study was to determine the Learning Transformation of Multimedia-Based Character Education in the Era of Society 5.0 and what the supporting and inhibiting factors in the application of Character Education Learning Transformation in the Era of Society 5.0 at Ar-Rahman Islamic Boarding School Palembang, This research includes using qualitative research methods. Data was obtained using interviews and observations. The data analysis techniques used in this study are data collection, data reduction, data presentation, conclusion drawing, and leveraging. The results of this study indicate that the implementation of multimedia-based character education learning transformation in the era of Society 5.0 takes place through the stages of habituation of students to behave well in the teaching and learning process using multimedia, practicing teacher advice, modeling good behavior exemplified by the teacher, and obeying the rules of the teacher in learning using multimedia. Supporting factors for implementing multimedia-based character education learning transformation in the era of Society 5.0 are school support, teacher support, students' willingness to learn using multimedia, and the existence of multimedia technology that students are familiar with. The inhibiting factors are the existence of bad people who deliberately damage the morals of the younger generation through bad applications, a less supportive environment, and the development of technology and communication that is growing rapidly.